2018
DOI: 10.24326/asphc.2018.5.15
|View full text |Cite
|
Sign up to set email alerts
|

CHANGES IN QUALITY INDICATORS OF MINIMALLY PROCESSED WRINKLED ROSE (Rosa rugosa Thunb.) PETALS DURING STORAGE

Abstract: Rosa rugosa petals, which have long been used in traditional medicine due to their attractive flavor and presence of bioactive components, are also commonly applied to produce minimally processed and nonthermally treated products with the addition of sucrose. Therefore, to ensure safety and high value of such products during storage, it is crucial to investigate changes in quality indicators. The examined material was non-thermally treated and homogenized petals of wrinkled rose with sucrose concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…The same authors also referred that b* values were higher in cultivars with white petals and lower in pink-flowered cultivars. Zawiślak and Michalczyk [ 14 ], in a study on the effect of sucrose addition and storage length of minimally processed products from R. rugosa petals, measured a b° value of −10.7 on fresh petals. The chroma (C°) was significantly influenced by the cultivars, with higher values recorded on cv.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The same authors also referred that b* values were higher in cultivars with white petals and lower in pink-flowered cultivars. Zawiślak and Michalczyk [ 14 ], in a study on the effect of sucrose addition and storage length of minimally processed products from R. rugosa petals, measured a b° value of −10.7 on fresh petals. The chroma (C°) was significantly influenced by the cultivars, with higher values recorded on cv.…”
Section: Resultsmentioning
confidence: 99%
“…Alba (4.41 and 2.14 mg/g). Zawiślak and Michalczyk [ 14 ] reported that R. rugosa petals contained β-carotene. Nowak et al [ 9 ], when investigating R. rugosa petals composition, determined the presence of carotenoids in a concentration of 1.39 µg g −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bunga mawar (Rosa damascena mill.) dalam beberapa penelitian dinyatakan bahwa petal bunga mawar memiliki kandungan metabolit sekunder yang dilaporkan memiliki aktivitas antioksidan, metabolit sekunder pada petal bunga mawar ini diketahui mengandung vitamin C yang tinggi yang berpotensi sebagai antioksidan (Sengui, Sener, & Ercisli, 2017;Zawiślak & Michalczyk, 2018). Penelitian tersebut menyebutkan bahwa antosianin mayor yang terdapat pada petal bunga mawar merah adalah senyawa Cyanidin 3,5-di-O-glucoside yang menunjukkan aktivitas antioksidan DPPH tinggi dengan kadar nilai IC50 55,2 µg/mL (Choiriyah, 2020).…”
Section: Pendahuluanunclassified